Head and neck sarcomas: clinical and histopathological presentation, treatment modalities, and outcomes. Issue 9 (1st August 2016) - Stavrakas, M; Nixon, I; Andi, K; Oakley, R; Jeannon, J P; Lyons, A; McGurk, M; Urbano, T Guerrero; Thavaraj, S; Simo, R
Abstract: Background: Sarcoma of the head and neck is a rare condition that poses significant challenges in management and often requires radical multimodality treatment. Objectives: This study aimed to analyse current clinical presentation, evaluation, management dilemmas and oncological outcomes. Methods: Computer records and case notes were analysed, and 39 patients were identified. Variables were compared using Pearson's chi-square test and the log-rank test, while survival outcomes were calculated using the Kaplan–Meier method. Results: The histopathological diagnosis was Kaposi sarcoma in 20.5 per cent of cases, chondrosarcoma in 15.3 per cent and osteosarcoma in 10.2 per cent. A range of other sarcomas were diagnosed in the remaining patients. The site of disease was most commonly sinonasal, followed by the oral cavity and larynx. Conclusion: Wide local excision with clear resection margins is essential to achieve local control and long-term survival. There is a need for cross-specialty collaboration in order to accrue the evidence which will be necessary to improve long-term outcomes.